Contribuição de fatores genéticos e agronômicos sobre a intensidade da brusone de trigo - Webber, Natália Forchezato (2020)
Wheat blast is caused by the fungus Pyricularia oryzae. The fungus can infect all the aboveground tissues of the plant, but the characteristic symptom of the disease is the partial or total discoloration of the spike. This study aimed was to evaluate the reaction of different wheat genotypes to P. oryzae in spikes, and to associate with production data, thus identifying materials with higher levels of resistance to blast. For this study, 14 wheat genotypes were selected, two susceptible and 12 resistant. The experiments were conducted in Patos de Minas, MG, Brazil. The genotypes were sown in 2014, with three repetitions and in three seasons, 2015, with four replications and in three seasons, and 2017 with three replications and in a single season, in a randomized block design. Blast incidence and severity, disease index, grain yield, and yield losses were evaluated. The variables were submitted to Analysis of variance and the interaction between sowing time and genotype was analyzed. Sowing season averages were compared using the Tukey test, with a 5% probability. Genotype averages were compared by the Scott-Knott test, with a 5% probability. Correlation analyzes among the variables were performed using Pearson's correlation coefficient. The disease incidence was the best parameter to evaluate the wheat resistance to blast and presented a significant correlation with grain yield (-0.81). Three groups were with different levels of incidence identified, and the lowest values ranged from 9.3 to 27.4% for 10 genotypes comprising BR 18. The lowest yield losses varied from 33.3 to 54.8% for 10 of the 14 genotypes evaluated. Yield losses were positively correlated to incidence (0.63) and negatively to grain yield (-0.70). The group with higher grain yield and lower yield losses includes BR 18, BRS Angico, PF 909, BRS 229, Embrapa 27, and CPAC 07340, which do not carry the 2NS/2AS translocation.